Species composition and abundance of fishes with seasonal fluctuations of rainfall and water level in vavuniya reservoir, sri lanka - Patrick, A.E.S.; Kuganathan, S.; Edirisinghe, U. (University of Jaffna, 2017)
Dramatic loss of freshwater fish bio-diversity and survival of un requirement of systemic surveys. Extreme hydro in dry zone aquatic resources such as Vavuniya reservoir, threatening fish species richness and abundance. Weekly filed surveys were made to collect biological, ecological and hydro composition and abundance in the catch were estimated by using random sampling at the landing site. Esomus thermoicos and Labeo lankae were the endemic freshwater fish species identified along with 16 indigenous and 8 exotic species. A significantly higher abundance of indigenous species was found in July and August 2013. periods, higher rainfall was observed but water level receded to medium level. August 2013 and March & July 2014), Puntius dorsalis (August 2013 and July 2014) and P. sarana (August, 2013) were observed during these periods. Higher catches of 2014. Mystus keletius and Heteropneustes fossilis showe keletius catch was higher in March and June and abundance during August 2013 and January 2014. Higher abundance was observed wi water level. Fish species composition and abundance were significantly different (p=.02) for each month of the year 2013 and 2014 with respect to monthly total rainfall and monthly mean water level. climatic factors play a significant role in fish species composition and abundance in tropical reservoirs.
Keywords: Species composition; Rainfall; Water level